Association of worker's mental health with changes in exercise time, going‐out time, and screen time (TV time, internet time, and game time) before and after the COVID‐19 pandemic: A cross‐sectional study - Yutaro Okawa; Shinichi Iwasaki; Yasuhiko Deguchi; Yoko Nakamichi; Yuki Uesaka; Shohei Okura; Kunio Maekubo; Koki Inoue (Wiley, 2024)
Abstract The coronavirus disease 2019 (COVID‐19) pandemic and government regulations have affected the daily lives and mental health of individuals worldwide. This study aimed to determine how much the change in time spent on exercise (exercise time), outdoor activities ("going‐out" time), and screen usage (screen time) before and after the COVID‐19 pandemic has affected mental health (depression, anxiety, and insomnia). In June 2021, during the third wave of the COVID‐19 pandemic, a web‐based, cross‐sectional survey was conducted in Japan through an online research company. A total of 824 workers participated in this study. Depression, anxiety, and insomnia were assessed using the Patient Health Questionnaire‐9, General Anxiety Disorder‐7, and Insomnia Severity Index, respectively. The symptoms of depression were associated with age and decreased exercise time. Symptoms of anxiety were associated with not decreased going‐out time. Symptoms of insomnia were associated with reduced exercise time. The results indicated that during the COVID‐19 pandemic, an increase in exercise time could have prevented depression and insomnia. Similarly, a decrease in going‐out time could have prevented anxiety. Furthermore, in the event of future outbreaks of unpredictable infections, such as COVID‐19, decreased going out and increased exercise may help maintain mental health.